Effects of Plant Hormones, Metal Ions, Salinity, Sugar, and Chemicals Pollution on Glucosinolate Biosynthesis in Cruciferous Plant - Liu, Zeci; Wang, Huiping; Lv, Jian; Luo, Shilei; Hu, Linli; Wang, Jie; Li, Lushan; Zhang, Guobin; Xie, Jianming; Yu, Jihua (Frontiers in Plant Science, 2022)
Cruciferous vegetable crops are grown widely around the world, which supply a multitude of health-related micronutrients, phytochemicals, and antioxidant compounds. Glucosinolates (GSLs) are secondary metabolites found widely in cruciferous vegetables, which are not only related to flavor formation, but also has anti cancer, disease-resistance, and insect resistance properties. The content and components of GSLs in the Cruciferae are not only related to genotypes and environmental factors, but also are influenced by hormones, plant growth regulators, and mineral elements. This review discusses the effects of different exogenous substances on the GSL content and composition, and analyzes the molecular mechanism by which these substances regulate the synthesis of GSLs. Based on the current research status, future research directions are also proposed.